2015
DOI: 10.1186/s12864-015-2292-8
|View full text |Cite|
|
Sign up to set email alerts
|

Liver transcriptomic networks reveal main biological processes associated with feed efficiency in beef cattle

Abstract: BackgroundThe selection of beef cattle for feed efficiency (FE) traits is very important not only for productive and economic efficiency but also for reduced environmental impact of livestock. Considering that FE is multifactorial and expensive to measure, the aim of this study was to identify biological functions and regulatory genes associated with this phenotype.ResultsEight genes were differentially expressed between high and low feed efficient animals (HFE and LFE, respectively). Co-expression analyses id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
160
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(195 citation statements)
references
References 68 publications
22
160
1
6
Order By: Relevance
“…In support of our results, it has already been shown that the more efficient Nelore steers of this population had significantly lower liver and internal fat proportions and lower extracted amounts of intramuscular fat compared to the less efficient steers20. Also supporting our findings, a study observed differentially co-expressed genes related to fatty acid metabolic processes in Nelore animals divergent for RFI, indicating the differential metabolism of lipids between these divergent feed efficiency groups44.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In support of our results, it has already been shown that the more efficient Nelore steers of this population had significantly lower liver and internal fat proportions and lower extracted amounts of intramuscular fat compared to the less efficient steers20. Also supporting our findings, a study observed differentially co-expressed genes related to fatty acid metabolic processes in Nelore animals divergent for RFI, indicating the differential metabolism of lipids between these divergent feed efficiency groups44.…”
Section: Discussionsupporting
confidence: 91%
“…Mitochondria play a major role as energy suppliers and ROS regulators42. Furthermore, other studies with cattle4344, including our previous study investigating global liver gene expression changes in Nelore steers from this population12 demonstrate that less feed efficient animals exhibit gene expression differences that are related to the modulation of conditions of oxidative stress.…”
Section: Discussionmentioning
confidence: 84%
“…After publication of the original article [1], it came to the authors' attention that there were errors in the author list. The given name of Joanir P. Eler had been inadvertently misspelled, and Saulo Luz Silva was incorrectly listed as Paulo L. Silva.…”
Section: Erratummentioning
confidence: 99%
“…These trials were carried out in individual pens with either GrowSafe or Calan Gates for recording the feed intake. Further details about the animals, phenotypes, facilities, experimental diets, and management procedures are available in Santana et al (2012), Gomes et al (2013), and Alexandre et al (2015).…”
Section: Phenotypic Datamentioning
confidence: 99%
“…In all the experiments, animals were handled in accordance with the guidelines of the Brazilian College of Animal Experimentation (COBEA). Phenotypic data and DNA samples were taken from each of the experiments, which had been approved by the respective Ethics Committees for each study (Santana et al, 2012;Gomes et al, 2013;Alexandre et al, 2015).…”
Section: Ethical Statementmentioning
confidence: 99%